SOME ZYGNEMATALEAN ALGAE FROM NORTH-EASTERN UTTAR PRADESH, INDIA - Misra, P. K.; Srivastava, A. K. (Ecoprint: An International Journal of Ecology, 2004)
Present communication deals with 9 taxa of order Zygnematales (Conjugales by Fritsch 1935, Zygnemales by Randhawa 1959) of class Chlorophyceae. Genera Mougeotia Ag. and Zygnema Ag. each with 2 species while Spirogyra Link with 5 species are well flourishing along with other group of algae in different localities of North-Eastern, U.P.Morpho-taxonomic descriptions of species like Mougeotia sphaerocarpa Wolle, Mougeotia sp., Spirogyra bichromatophora (Randhawa) Transeau, S. biformis Jao, S. parvula (Trans) Czurda, S. hymerae Britton and Smith, Spirogyra sp., Zygnema insigne (Hassall) Kuetz and Z. vaucherii Ag. are mainly based on length and breadth of vegetative filaments, chloroplast shape, number, direction of turning, conjugation type, shape, size and position of zygospore. Two taxa, Spirogyra sp. and Mougeotia sp. have been described under open nomenclature system as the fertile parts are not preserved.These algae have been collected from various aquatic habitats of Bahraich and Gonda district of North-Eastern U.P., constitute new record for the area.Key words: Freshwater, chlorophyceae, zygnematalean algae, U.P.Ecoprint Vol.11(1) 2004.